Vector competence of the invasive mosquito species Aedes koreicus for arboviruses and interference with a novel insect specific virus - Jansen, Stephanie; Cadar, Daniel; Lühken, Renke; Pfitzner, Wolf Peter; Jöst, Hanna; Hoffmann, Sandra; Helms, Michelle; Zibrat, Branka; Kliemke, Konstantin; Becker, Norbert; Vapalahti, Olli; Rossini, Giada; et al. (Viruses, 2021)
The global spread of invasive mosquito species increases arbovirus infections. In addition to the invasive species Aedes albopictus and Aedes japonicus, Aedes koreicus has spread within Central Europe. Extensive information on its vector competence is missing. Ae. koreicus from Germany were investigated for their vector competence for chikungunya virus (CHIKV), Zika virus (ZIKV) and West Nile virus (WNV). Experiments were performed under different climate conditions (27 ± 5 °C; 24 ± 5 °C) for fourteen days. Ae. koreicus had the potential to transmit CHIKV and ZIKV but not WNV. Transmission was exclusively observed at the higher temperature, and transmission efficiency was rather low, at 4.6% (CHIKV) or 4.7% (ZIKV). Using a whole virome analysis, a novel mosquito-associated virus, designated Wiesbaden virus (WBDV), was identified in Ae. koreicus. Linking the WBDV infection status of single specimens to their transmission capability for the arboviruses revealed no influence on ZIKV transmission. In contrast, a coinfection of WBDV and CHIKV likely has a boost effect on CHIKV transmission. Due to its current distribution, the risk of arbovirus transmission by Ae. koreicus in Europe is rather low but might gain importance, especially in regions with higher temperatures. The impact of WBDV on arbovirus transmission should be analyzed in more detail.
Gesehen am 19.07.2022